The Company’s Perspective on Affiliate Marketing Programs in Increasing Brand Awareness and Conversion at PT. Paragraf Labs Indonesia - Sanjaya, Moch Muhyi (Selekta Manajemen: Jurnal Mahasiswa Bisnis & Manajemen, 2025)
This study explores how affiliate marketing strategies can enhance brand awareness and conversion rates at PT. Paragraf Labs Indonesia. Despite its reliance on affiliate marketing, the company faces challenges such as weak management structures, limited performance tracking, and inconsistent affiliate results. Using qualitative methods such as interviews with five staff members and field observations. The research evaluates how structured management tools like performance tracking systems and statements of work (SOW) can improve accountability. It also analyzes the role of storytelling-based content in boosting consumer trust and engagement. Findings show that applying structured guidelines, optimizing affiliate selection and incentives, and using emotional storytelling significantly strengthen brand awareness and conversions. The study offers practical insights for marketers seeking to improve affiliate program effectiveness.